Radiation Exposure–Induced Changes in the Immune Cells and Immune Factors of Mice With or Without Primary Lung Tumor. Issue 2 (18th May 2020) - Pan, Shuxian; Wang, Jingjie; Wu, Anqing; Guo, Ziyang; Wang, Ziyang; Zheng, Lijun; Dai, Yingchu; Zhu, Lin; Nie, Jing; Hei, Tom K.; Zhou, Guangming; Li, Youchen; et al.
Recent studies have demonstrated that radiation activates in situ antitumor immunity and consequently induced a synergistic effect of radiotherapy and immunotherapy. However, studies related to radiation-induced changes in immune system of tumor-bearing mice are limited, which are of great significance to improve the efficacy of radioimmunotherapy. In this study, we first established a primary lung tumor mouse model using urethane. Then part of the right lung of the mouse was exposed to X-ray irradiation with a computed tomography–guided small animal irradiator and the changes of immune cells in both peripheral blood and spleen were determined by flow cytometry. Besides, the levels of both cytokines and immunoglobulins in mouse serum were detected by a protein chip. We found that B lymphocytes increased while CD8 + T lymphocytes reduced significantly. Interleukin-3 (IL-3), IL-6, regulated upon activation, normally T-expressed, and presumably secreted factor (RANTES), and vascular endothelial growth factor (VEGF) were found to be decreased after tumor formation, and the similar results have also been observed with kappa, IgG3, IgE, IgM, and IgG2a. After irradiation, lower concentrations of IgD, kappa, and IgM were found in the serum. Our findings indicate that localized tumor irradiation caused some obvious changes like inhibiting the ability of innate immunity, and these changes may be useful in predicting prognosis.